MANAGING CHIARI II MALFORMATION IN A COMPLEX PEDIATRIC CASE: A REPORT (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Chiari II malformation (CM-II) is an innate CNS condition in which the medulla oblongata, pons, fourth ventricle, and cerebellum move lower inside the spinal canal. This abnormality is one of the leading causes of neonatal and infant death. The diagnosis of CM-II in the patient necessitates a thorough understanding of the findings. In this case report, we demonstrate a Chiari malformation II identified by MRI of the brain and spine. This case also highlights the need for neuropsychological evaluation in CM-II in terms of providing guidance for psychoeducation and psychotherapy.